PROBLEM-BASED GROUP DISCUSSION: AN EFFECTIVE ELT TECHNIQUE TO IMPROVE VOCATIONAL HIGH SCHOOL STUDENTS’ TRANSACTIONAL SPEAKING SKILLS - Kaharuddin Kaharuddin; Ananda Rahmadana (JURNAL ILMU BUDAYA, 2020)
In this millennial era, English speaking skills are very necessary for young learners, especially for Vocational High Schools students. However, few teachers still have difficulties in choosing the right technique to teach the speaking skills. Consequently, students feel that speaking is the hardest skill in English. This paper is aimed at discussing how to improve the students’ transactional speaking skills (group discussion) using problem-based group discussion technique at Vocational High School 5 Gowa. A quantitative research design was used to carry out this study with support from the data collection instrument i.e. speaking video test (group discussion). The design of this study conducted using a quasi-experimental with nonequivalent control group design. Twenty (20) students in two classes i.e. ten students for the experimental class and ten students for the controlled class of the intermediate level were purposively selected to participate in this study. The results of this study showed that the problem-based group discussion technique is able to improve students’ transactional speaking skills. It was proved by the result of the statistical analysis of the level significance P = 0.05 with the degree of freedom (df) = 9 indicated that the t-test values of the students’ transactional speaking skills (3.498) was higher than the t-table value (2.262). The outcome of this research indicates that this technique is effectively able to improve the students’ transactional speaking skills in exchanging information, taking a part in formal discussions and even learning to work in real-life situations